The Calcium Modulator Nifedipine Exerts Its Antiaggregatory Property via a Nitric Oxide Mediated Process - Berkels, R; Klaus, W; Boiler, M; Rösen, R (Thrombosis and Haemostasis, 1994)
The in vitro effect of nifedipine, a calcium channel blocker of the dihydropyridine (DHP) type, on platelet aggregation was reinvestigated considering especially the capability of platelets to form endogenous nitric oxide (NO). We studied the dose-dependent antiaggregatory property of nifedipine in porcine platelet rich plasma. Aggregation was stimulated by collagen (7.5 ¼g/ml). Nifedipine inhibited collagen-induced platelet aggregation with an IC50 of 380 nmol/1. The antiaggregatory effect of nifedipine could be significantly diminished by N-nitro-L-arginine (NNA) in a concentration dependent manner, whereas oxy haemoglobin (4 ¼M), a NO scavenger, totally abolished the effect of nifedipine. L-Arginine, the precursor of NO, dose-dependently inhibited the collagen-induced platelet aggregation but did not potentiate the effects of nifedipine. Therefore, we propose that in platelet rich plasma the nifedipine induced inhibition of platelet aggregation is mediated by NO, a potent endogenous inhibitor of aggregation. We could confirm this hypothesis by measuring NO directly with a specific electrode.